2015
DOI: 10.1063/1.4907609
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic capacitance and Faraday cage behavior of carbon nanotube forests

Abstract: Articles you may be interested inUltrasonicated double wall carbon nanotubes for enhanced electric double layer capacitance Appl. Phys. Lett.Carrier density and quantum capacitance for semiconducting carbon nanotubes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…2. Measurement of the capacitance of CNT forests in our recent previous work [39] confirmed that the capacitance of a similar CNT forest micropillar is dominated by outer surfaces, and the electric field only penetrates several microns into the forest. Therefore, when force is applied by the electric field, the penetration depth is limited and the observed orientation change of the CNTs (see below) is restricted to the top surface where the field is greatest.…”
Section: Mechanism Of Electrostatic Loadingsupporting
confidence: 53%
See 4 more Smart Citations
“…2. Measurement of the capacitance of CNT forests in our recent previous work [39] confirmed that the capacitance of a similar CNT forest micropillar is dominated by outer surfaces, and the electric field only penetrates several microns into the forest. Therefore, when force is applied by the electric field, the penetration depth is limited and the observed orientation change of the CNTs (see below) is restricted to the top surface where the field is greatest.…”
Section: Mechanism Of Electrostatic Loadingsupporting
confidence: 53%
“…We further note that the CNT forest behaves as a Faraday cage [39], i.e., the electrostatic force acts only on its external surface, as indicated schematically by the red color in Fig. 2(d).…”
Section: Electrostatic Force Calculationmentioning
confidence: 93%
See 3 more Smart Citations